Experience in vegetable waste burning in furnace block TBR-2.0 - A. V. Golubkovich; L. I. Belen'kaya; A. N. Dadyko; V. B. Lovkis (Сельскохозяйственные машины и технологии, 2017)
There are various types of furnace systems with use of alternative and local fuels with the fluidized bed for grain drying. A low-quality fuel burns in the fluidized bed better, than in dense one. As well emissions of nitrogen oxides decrease very much. Ecological, operational and economic benefits of these fire chambers are certain. They are especially perspective for combustion of low-grade fuels and various waste (for example, waste of agricultural production) in a ciclonic and vortex layer. The distinctive feature of such fire chambers is availability of vortex contours in the burning camera that increases efficiency of burning process. The authors carried out testing of the furnace block with grain dryer SZT-30 at OOO «Borisoglebsky MEZ» (Voronezh region) at corn and sunflower seeds drying. We burned sunflower peelings with the lowest calorific power of 14 MJ and 17 MJ at 1 furnace block capacity of 100, 210, 230, 250, 280, 320 and 380 kg per hour. The set of two furnace blocks (TBR-2.0) operating with sunflower peelings which are characterized by the lowest calorific power at least 17 MJ per 1 kg will provide necessary capacity of the dryer SZT-30 when grain and seeds drying. The maximum capacity of the unary thermal block TBR-2.0 should not exceed 1.5 MW. As well the maximum efficiency is reached, and extent of air heating provides functioning of the dryer at a temperature of external air not below 5 degrees Celsius. The economy and safe mode of operation of the furnace block can be provided in case of capacity 0.8-1.3 MW and 1.2-1.5 times air-fuel ratio. In this case emissions of nitrogen oxides are less than permitted value and equal 0.6-0.7 g per 1 cubic meter.